Sub-state entities in eu law: Changes and challenges - Alves, Luísa Verdelho (Journal of Business and Legal Sciences / Revista de Ciências Empresariais e Jurídicas, 2018)
In a “post-state” era, sub-state political communities face new challenges. Modern constitutionalism resorted to various political and territorial forms to ensure the autonomy of certain social communities; in many cases, uniting different nations under the same State. But the integration of States into transnational political communities had profound implications on the sub-state levels of government. In the European context, it is now widely recognized that the process of integration unleashed centripetal forces. This article revisits the effects of European integration in the internal distribution of powers and examines the novelties introduced by the Lisbon Treaty regarding the position, the powers, and the rights of substate communities in EU Law.